Vous êtes sur la page 1sur 2

# Department of Mathematics, NIT Warangal

MA 201 :: Mathematics - III (for II B.Tech. EEE, Chem, MME & BioTech)

## Problem Sheet - 02 Fourier Transforms

0, t < 0; 1 1. Find the Fourier integral representation of f (x) = , t = 0; Verify the representation directly 2 eat , t > 0. at the point t = 0. sin t, 0 < t ; 2. Applying the Fourier Sine Integral formula to the function f (t) = , show that 0, t > . sin t, 0 < t < ; sin t sin 2 d = 0, 1 2 0 t > . 3. Applying the Fourier Cosine Integral formula to the function f (t) = 1 when 0 t < 1 and f (t) = 0 1 , 0 t < 1; 2 sin cos t 1 d = when t > 1, show that , t = 1; 4 0 0, t > 1. 4. Using appropriate Fourier Integral formulae, show the following: cos x, 0 < |x| < ; cos cos x 2 2 2 (a) d = 2 1 0 0, |x | .
2

(b)
0

( 2

(c) eax

+ 2) cos x

(a, b > 0)

0

cos pt a2 + t2

dt =

ea|p| .
2 2 . (1+ 2 )2

## (b) Deduce also that the Fourier Transform of xe|x| is i

6. Find the Fourier Cosine Transform of the function eax , a > 0. (a) Use it to nd the Fourier Transform of ea|x| cos bx. cos px (b) Show also that dx = eap , (p 0) 2 2 a +x 2 0 1 (c) Hence, nd the Fourier Cosine Transform of 2 . a + x2 7. Find the Fourier Sine Transform of the function eax , a > 0.

## (a) Using it, show that

0

x sin px a2 + x2

dx =

eap , (p > 0) x + x2 .

## (b) Hence, nd the Fourier Sine Transform of

a2 1

8.

a |x|, |x| < a; . Find the Fourier Transform of f (x) = 0, |x| > a > 0.
2

sin2 t t2

dt =

, and that
0

sin4 t t4
2 x2

dt =

.
x2 2

2 x2

2 x 2

2 x2

## . Hence, also show that e

x2 2

is

self-reciprocal under FCT and that xe 11. Find the FST of eax x , a > 0.

0

, a > 0.

## 3( 2 ) . 14. Find the function f (x) whose FT is 2 sin ( 2 )

1, |x| < a; 15. Find the FT of f (x) = . Hence, nd FT of f (x) 1 + cos 0, |x| > a. 16. Using the FCT and FST of eax , nd FST and FCT of xeax . 17. Find the FST and FCT of xa1 , 0 < a < 1. Hence, deduce that transforms. Also, nd the FT of 1 .
|x| 1 x

x a

(a)
0

1 (x2 + a2 )2 x2

dx =

## 4a3 4a = 2ab(a + b) 2(a + b)

(b)
0

(c)
0

(x2 + a2 ) dx (x2 + x2

dx = 2 +

a2 )(x2

b2 )

(d)
0

(x2 + a2 )(x2 + b2 )

dx =

t=

f (t)e

it

f ( )e

ix

t=0

fc ( ) cos xd
=0

t=0

fs ( ) sin xd
=0